SUTILEZAS ENTRE CIÊNCIA, POLÍTICA E VIDA PRÁTICA: ALFABETIZAÇÃO EM UMA COMUNIDADE REMANESCENTE QUILOMBOLA - Grokorriski, Carlos Ricardo (2012)
This dissertation aims to describe the dynamics of the relations between an specific governamental action, the “Paraná Alfabetizado” program, whose function is the alphabetization of the young, adults and elderly, and a remaining quilombola community (CRQ), in this case, the Sutil community. The theoretical base is constitued from the concepts of ‘dialogicity/conscientization’ in Paulo Freire; and ‘disciplinary matrix/ historical consciousness’ in Jörn Rüsen. Both (concepts/authors) share similar theories on the relations between the spheres of knowledge and practical life. At the same time, other referentials that contribute to some aspects of this text were utilizes. The research is qualitative and the gathering of data was developed by exploratory survey followed by interviews. Among the main contribution of this research are: a reflection on the identity of the community, its relations with the state institution, as well as the possibilities of projection in the future. The contributions of this work are given in order to provide opportunities for community intervention from an epistemological model that considers the integration of specialized knowledge, public sphere as political action management and practical life of the community.